Pancasila dan Penguatan Hukum Tata Negara Dalam Era Demokrasi: Pancasila and Strengthening Constitutional Law in the Era of Democracy - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya ; Nabila Aprilia Nur Azizah; Nina Faris Effendi; Nova Layla Rahmadani (Litera Academica Publishing, 2024)
This study discusses the strengthening of constitutional law based on Pancasila in indoensia’s modern democratic era. Panncasila, as the foundation of the state, embodies values that should guide the formulation and implementation of laws, particulary in safeguarding justice, unity, and social welfare. However, the application of Pancasila’s values in constitutional law still faces several challenges, including weak law enforcement institutions, high levels of corruption, social inequality, and limited public participation in the democratic process. This study analyzes the necessary efforts to strengthen constitutional law through institutional reform, combating corruption, increasing public participation, strengthening the Constitutional Court, implementing fair economic redistribution policies. Drawing on expert opinions and recent data, this research offers systemic solutions aimed at achieving the supremacy of law grounded in Pancasila’s values. The conclusion emphasizes the importance of synergy between the government, law enforcement intitutions, and society in carrying out legal and democratic reforms in Indonesia.